Luminescent (Er,Ho)(2)O-3 thin films by ALD to enhance the performance of silicon solar cells - Ghazy Amr; Safdar Muhammad; Lastusaari Mika; Aho Arto; Tukiainen Antti; Savin Hele; Guina Mircea; Karppinen Maarit (ELSEVIER, 2022)
We have fabricated luminescent (Er,Ho)2O3 thin films by atomic layer deposition (ALD) and studied their capability to enhance the performance of state-of-the-art single-junction c-Si bifacial solar cells. The films convert IR photons (e.g. 1523 nm) by threeand two-photon upconversion process to emit visible-light in the 400-700 nm range. When the films were coupled with solar cells, similar to 3% improvement in the short-circuit current density (620 +/- 5 to 638 +/- 5 mAcm-2) was recorded under a simulated solar excitation equivalent to 16 suns. These findings highlight a potential of ALD for the design and fabrication of luminescent coatings for practical solar cell devices.